Air pollution during growth accounting for governance and vulnerability - Hamilton, Kirk 1951-; Dasgupta, Susmita 1961-; Pandey, Kiran; Wheeler, David 1946- (World Bank, 2004)
"New research on urban air pollution casts doubt on the conventional view of the relationship between economic growth and environmental quality. This view holds that pollution automatically increases until societies reach middle-income status because poor countries have neither the institutional capacity nor the political commitment necessary to regulate polluters. Some policymakers and researchers have cited this model (called the "environmental Kuznets curve," or EKC) when arguing that developing countries should "grow first, clean up later." However, new evidence suggests that the EKC model is misleading because it mistakenly assumes that strong environmental governance is not possible for poor countries. As the authors show in this paper, the empirical relationship between pollution and income becomes much weaker when measures of governance are added to the analysis. Their results also suggest that previous research has underestimated the effect of geographic vulnerability (climate and terrain factors) on air quality. The authors find that weak governance and geographic vulnerability alone can account for the crisis levels of air pollution in many developing country cities. When these factors are combined with income and population effects, the authors have a sufficient explanation for the fact that some cities already have air quality comparable to levels in OECD urban areas. To summarize, their results suggest that the maxim "grow first, clean up later" is too simplistic. Appropriate urban growth strategies can steer development toward cities with lower geographic vulnerability, and governance reform can reduce air pollution significantly, long before countries reach middle-income status.
Includes bibliographical references. - Title from PDF file as viewed on 9/8/2004
Keywords: Wirtschaftsentwicklung; Air -- Pollution; Economic development